Influence of Enterprise Resource Planning System Quality on Employees’ Psychological Empowerment and Organizational Commitment: An Empirical Study on the Arab Potash Company - Almahamid, Soud; Al-Kasasbeh, Mouhammd (Jordan Journal of Business Administration, 2018)
This study aims to show the influence of enterprise resource planning system (hereafter called ERP) on employees’ psychological empowerment and organizational commitment in the Arab Potash Company. The study sample consisted of all managers, heads, supervisors and workers who are end - users of ERP. In order to achieve the objectives of the study, a questionnaire was developed based on related studies. It consisted of (63) statements and was distributed to the research sample that was composed of (120) end-users, where (100) questionnaire forms were retrieved. Only (90) questionnaire forms were suitable for further analysis, representing (75%) of the distributed questionnaire forms. The study arrived at a set of results, the most important of which is that there is an influence for ERP quality on employee psychological empowerment and organizational commitment. There is an influence for employees’ psychological empowerment on employees’ organizational commitment. There is a partial mediating role for employees’ psychological empowerment in the impact of ERP quality on employees’ organizational commitment. The study recommends that managers at the Arab Potash Company should enhance employees’ psychological empowerment by ensuring a high ERP quality, along with its information quality and service quality.